Solid acid catalyst as well as preparation method and application thereof
By preparing lignin-based carbon-based solid acid catalysts, the problems of serious corrosion of equipment and environmental pollution in the prior art are solved, and efficient and environmentally friendly 5-hydroxymethylfurfural preparation is achieved.
Patent Information
- Application Number
- CN202411402525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-03-11
AI Technical Summary
In the existing 5-hydroxymethylfurfural preparation process, acidic catalysts have severe corrosion to the equipment, and the waste acid solution after the reaction is difficult to deal with, which is easy to cause pollution to the environment.
It is provided a lignin-based carbon-based solid acid catalyst prepared by carbonization, activation and sulfonation treatment, and has the advantages of easy separation, weak corrosiveness, recyclability and high catalytic efficiency.
The solid acid catalyst can catalyze the conversion of glucose, fructose, etc. with high selectivity to prepare 5-hydroxymethylfurfural, avoid the corrosion problem of traditional catalysts, simplify the treatment of waste acid liquid, reduce environmental pollution, and have good catalytic stability and reusability.
Smart Images

Figure CN119588377A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a solid acid catalyst and a preparation method and application thereof. Background Art
[0003] 5-Hydroxymethylfurfural (5-hydroxymethylfurfural or HMF), also known as hydroxymethylfurfural, is a renewable and widely used platform compound with a molecular formula of C6H6O3. In addition to a five-membered ring, the molecule also contains a hydroxymethyl group and an aldehyde group. The presence of these two groups enables HMF to undergo hydrogenation, esterification, hydrolysis, polymerization and other reactions. So far, the main method for preparing HMF in industry is direct dehydration and conversion of monosaccharides or polysaccharides, such as glucose, fructose, sucrose, starch and cellulose.
[0004] The commonly used catalysts for producing HMF have more or less disadvantages such as serious corrosion to equipment, difficulty in handling waste acid after the reaction, and easy to cause serious pollution to the environment.
[0005] Therefore, it is very necessary to provide a catalyst that can improve the above shortcomings. Summary of the invention
[0006] In view of the problem that the acid catalyst in the existing 5-hydroxymethylfurfural preparation process has high requirements for reaction equipment and serious corrosion, the present invention provides a new type of lignin-based carbon-based solid acid catalyst to replace the acid catalyst to catalyze fructose dehydration to prepare 5-hydroxymethylfurfural. The solid acid catalyst has the advantages of easy separation, weak corrosion, recyclability, high catalytic efficiency, etc., can highly selectively catalyze the conversion of glucose, fructose, etc. to prepare 5-hydroxymethylfurfural, and has potential application value.
[0007] The invention provides a preparation method of a solid acid catalyst, which comprises the following steps: carbonizing lignin to obtain a carbon-based carrier; placing the carbon-based carrier in a plasma modification instrument, evacuating the air, and then introducing gas for activation treatment to obtain a lignin carbon-based material; and sulfonating the lignin carbon-based material to obtain the solid acid catalyst.
[0008] Furthermore, the equipment used for the carbonization treatment is a muffle furnace, the temperature is set to 300° C., and the carbonization time is 3 h to 5 h.
[0009] Furthermore, the vacuum degree in the plasma modification instrument after evacuation is 5Pa.
[0010] Furthermore, the gas used for the activation treatment is selected from at least one of oxygen, nitrogen, carbon dioxide and air; when the gas is introduced for activation treatment, the vacuum degree in the plasma modifier is 20Pa, the RF power is set to 160W, and the treatment time is 3min to 5min.
[0011] Furthermore, the gas used in the sulfonation treatment is sulfur dioxide, the vacuum degree in the plasma modification instrument during the sulfonation treatment is 20Pa-50Pa, the radio frequency power is set to 140W-170W, and the treatment time is 2min-8min.
[0012] Furthermore, the sulfonation treatment specifically includes: SO2 ventilation volume is 40Pa, the radio frequency power of the plasma modification instrument is 170W, and after treating for 3 minutes, the lignin carbon-based material is turned over and treated for another 3 minutes.
[0013] The present invention also provides a solid acid catalyst prepared by the above-mentioned method for preparing the solid acid catalyst.
[0014] The present invention also provides the use of the solid acid catalyst as described above in the field of preparing 5-hydroxymethylfurfural.
[0015] Further, the preparation of 5-hydroxymethylfurfural comprises the following steps: 1) adding fructose and the solid acid catalyst to a solvent and mixing them, and heating the mixture in a closed container for reaction; 2) cooling the closed container to room temperature by ice bath, and then filtering to separate the solid and the liquid to obtain the 5-hydroxymethylfurfural; wherein the solvent comprises an organic solvent and water in a volume ratio of 4:1 to 6:1; the organic solvent is selected from at least one of dimethyl sulfoxide, acetone, tetrahydrofuran, and methyl isobutyl ketone; the temperature of the heating reaction is 160°C to 190°C, and the reaction time is 5min to 100min. It should be noted that the filtering to separate the solid and the liquid in the step refers to the solid acid catalyst and the solid impurities that may be formed during the reaction, and the liquid refers to the reaction liquid, which contains the product 5-hydroxymethylfurfural, the unreacted substrate fructose, and the by-products generated during the reaction.
[0016] Furthermore, the method further comprises washing and drying the obtained solid and recycling it as a solid acid catalyst; preferably, the fructose is specifically hexose; preferably, the mass ratio of the hexose to the solid acid catalyst is 1:(0.01-0.5); preferably, the amount of the hexose substrate added is 0.02 g / mL-0.1 g / mL. It is understood that the amount of substrate added is the mass concentration of fructose in the reaction solution.
[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:
[0018] 1. The solid acid catalyst prepared by the present invention has a simple preparation process, multiple sources of raw materials, and can be mass-produced; and in the process of catalyzing the conversion of fructose into HMF, the catalytic efficiency is good. This solid acid catalyst avoids the danger of using concentrated sulfuric acid in the traditional process, greatly shortens the time of the sulfonation process, and can greatly improve production efficiency.
[0019] 2. Compared with the traditional solid acid preparation method, the present invention greatly shortens the reaction time and provides a new way for the preparation of solid acid catalysts.
[0020] 3. The present invention can effectively improve the catalytic activity of the catalyst by improving the dispersibility of the active components.
[0021] 4. Compared with other modification technologies, the present invention has significant advantages such as low operating temperature, high modification efficiency and short preparation time. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the prior art description in the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A flow chart of the preparation and application of the solid acid catalyst provided by the present invention;
[0024] Figure 2 The XPS characterization diagrams of the solid acid catalyst and the lignin raw material in Example 1 are compared;
[0025] Figure 3 This is a comparison of infrared characterization images of the solid acid catalyst and the lignin raw material in Example 1;
[0026] Figure 4 This is the recycling performance of the solid acid catalyst in Example 5. DETAILED DESCRIPTION
[0027] The inventors have found that the commonly used catalysts for producing HMF in the prior art mainly include inorganic acid catalysts, metal chlorides and solid acid catalysts. Inorganic acid (phosphoric acid, sulfuric acid, hydrochloric acid) is widely used in acid-catalyzed reactions because of its low cost and simple operation, but it also has many disadvantages, such as serious corrosion of equipment by inorganic acid, difficulty in handling waste acid liquid after reaction, and easy to cause serious pollution to the environment. These problems limit the large-scale application of inorganic acid to a certain extent. Metal chlorides also have good effects in biomass conversion, such as CrCl2, AlCl3, SnCl4, etc., which have excellent catalytic performance for glucose degradation to prepare HMF, which may be because they can promote the key reaction of glucose isomerization, but most metal chlorides are toxic and threaten the environment and human health. Compared with inorganic acid catalysts, solid acid catalysts have the advantages of easy separation, recyclability, and low corrosion to equipment, and have been widely studied in the fields of catalysis and chemical industry in recent years.
[0028] Non-thermal plasma (NTP) technology has shown great potential in catalyst modification due to its clean and efficient characteristics. Studies have shown that NTP technology can effectively modify the inner and outer surfaces of catalysts and improve the dispersibility of active components, thereby effectively improving the catalytic activity of catalysts. Compared with other modification technologies, NTP technology has significant advantages such as low operating temperature, high modification efficiency and short preparation time.
[0029] In recent years, the research on solid acid in biomass conversion has received extensive attention at home and abroad. After the catalysis is completed, the solid acid catalyst can be well separated from the reaction liquid, which simplifies the subsequent reaction liquid treatment process, reduces the treatment requirements, and has technical feasibility.
[0030] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0031] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.
[0032] The present invention provides a method for preparing a solid acid catalyst, such as Figure 1 As shown, the preparation method includes the following steps: carbonizing lignin to obtain a carbon-based carrier; placing the carbon-based carrier in a plasma modification instrument, evacuating the vacuum, and then introducing gas for activation treatment to obtain a lignin carbon-based material; sulfonating the lignin carbon-based material to obtain the solid acid catalyst.
[0033] Specifically, the preparation of 5-hydroxymethylfurfural includes the following steps: 1) adding fructose and the solid acid catalyst into a solvent and mixing them, and heating them in a closed container for reaction; 2) cooling the closed container to room temperature by ice bath, and then filtering to separate the solid and the liquid to obtain the 5-hydroxymethylfurfural; 3) washing and drying the solid for later use.
[0034] The separated liquid was analyzed by HPLC.
[0035] The concentrations of fructose, 5-HMF, byproduct formic acid and levulinic acid were determined by HPLC, and the fructose conversion rate, 5-HMF yield and reaction selectivity were calculated according to the following formulas:
[0036] ①
[0037] ②
[0038] ③
[0039] Where: m1, m2 and m3 are the mass of added fructose, the mass of remaining fructose after reaction and the mass of generated 5-HMF, in g; M 果糖 and M HMF is the molar mass of fructose and 5-HMF, in g / mol.
[0040] It should be noted that the reaction selectivity refers to how many moles of the substrate fructose are converted into the target product 5-HMF, because in this catalytic reaction, fructose will not only produce HMF but also by-products such as formic acid and levulinic acid. Therefore, the higher the reaction selectivity, the better the catalytic effect of the catalyst.
[0041] The percentage yield of 5-hydroxymethylfurfural is calculated according to the following formula. It can be concluded that:
[0042]
[0043] More specifically, the present invention provides a method for preparing a solid acid catalyst and its application, comprising the following steps: 1) using a lignin-based carbon material as a carrier, preparing a sulfonated solid acid catalyst by plasma modification in an SO2 atmosphere; 2) adding the constructed new solid acid catalyst into a reactor to catalyze the conversion of fructose into 5-hydroxymethylfurfural; 3) after the reaction is completed, rapidly cooling in an ice-water bath, filtering, separating the reaction liquid from the catalyst, and recovering the catalyst.
[0044] Example 1: Preparation method of lignin-based carbon-based solid acid catalyst
[0045] Corn stalks (i.e., lignocellulose raw materials) were ground into a particle size of 40-60 mesh, washed and dried at 45°C to constant weight. Then, they were reacted in an organic solvent / water solution containing 0.8wt% oxalic acid at a solid-liquid ratio of 1:12 (w / w). The organic solvent was tetrahydrofuran, and the mass ratio of the organic solvent to water was 3:2. In a high-temperature and high-pressure stainless steel reactor, the reaction was carried out at 140°C for 1 hour using a magnetic stirring device. After the reaction was completed, the reactor was placed in an ice-water bath for rapid cooling, and filtered to obtain a filter residue and a filtrate. Then, fresh deionized water with a volume ratio of 4:1 was added to the filtrate to precipitate the lignin component in the filtrate, filter, and rinse the obtained solid residue with deionized water until neutral, and then dried in an oven at 45°C to constant weight.
[0046] The obtained lignin powder was carbonized in a muffle furnace at 300°C for 3h, and then the lignin-based carbon was placed in a plasma modifier, evacuated to 5Pa, and then O2 was introduced to 20Pa, and activated at a power of 160W for 3min. SO2 was introduced to sulfonate the lignin carbon-based material, and the SO2 ventilation volume was 40Pa, the modification time was 3min, and the plasma power was 170W. The material was taken out and turned over, and sulfonated again under the above conditions for a total of 6min to obtain a lignin-based carbon-based solid acid catalyst. Under the above conditions, the fructose conversion rate was 98.2%, the 5-HMF yield was 75.0%, and the reaction selectivity reached 76.9%.
[0047] Embodiment 2:
[0048] Lignin was extracted according to the method described in Example 1.
[0049] The obtained lignin powder was carbonized in a muffle furnace at 300 ° C for 3 hours, and then the lignin-based carbon was placed in a plasma modifier, evacuated to 5Pa, and then O220 Pa was introduced, and activated at a power of 160W for 3 minutes. The lignin carbon-based material was sulfonated by passing SO2, and the SO2 ventilation volume was 50Pa, the reaction time was 1min, and the plasma power was 140W. It was taken out and turned over, and sulfonated again under the above conditions for a total of 2 minutes to obtain a lignin-based carbon-based solid acid catalyst. Under the above conditions, the fructose conversion rate was 92.7%, the 5-HMF yield was 61.7%, and the reaction selectivity reached 67.2%.
[0050] Embodiment 3:
[0051] Lignin was extracted according to the method described in Example 1.
[0052] The obtained lignin powder was carbonized in a muffle furnace at 300°C for 3h, and then the lignin-based carbon was placed in a plasma modifier, evacuated to 5Pa, and then O220 Pa was introduced, and activated at a power of 160W for 3min. The lignin carbon-based material was sulfonated by passing SO2, and the SO2 ventilation volume was 30Pa, the reaction time was 2min, and the plasma power was 150W. It was taken out and turned over, and sulfonated again under the above conditions for a total of 4min to obtain a lignin-based carbon-based solid acid catalyst. Under the above conditions, the fructose conversion rate was 97.3%, the 5-HMF yield was 72.4%, and the reaction selectivity reached 76.4%.
[0053] Embodiment 4:
[0054] Lignin was extracted according to the method described in Example 1.
[0055] The obtained lignin powder was carbonized in a muffle furnace at 300°C for 3h, and then the lignin-based carbon was placed in a plasma modifier, evacuated to 5Pa, and then O220 Pa was introduced, and activated at a power of 160W for 3min. The lignin carbon-based material was sulfonated by passing SO2, and the SO2 ventilation volume was 40Pa, the reaction time was 2min, and the plasma power was 160W. It was taken out and turned over, and sulfonated again under the above conditions for a total of 4min to obtain a lignin-based carbon-based solid acid catalyst. Under the above conditions, the fructose conversion rate was 97.6%, the 5-HMF yield was 73.7%, and the reaction selectivity reached 76.1%.
[0056] Figure 2 The XPS characterization diagrams of the solid acid catalyst and lignin raw material in Example 1 are compared. It can be seen that the two signals displayed at 284.3eV and 531.9eV correspond to C1s and O1s, respectively. Compared with lignin, the O1S peak of LDSA-SO3H is significantly enhanced, which may be caused by the grafting of a large number of oxygen-containing groups on the surface of the solid acid during activation and sulfonation. In addition, a characteristic peak corresponding to S2p was observed at 168eV, indicating that the NTP modification successfully sulfonated the solid acid, and most of the S atoms exist in the form of -SO3H, which is consistent with the FTIR results.
[0057] Figure 3 This is a comparison of the infrared characterization images of the solid acid catalyst and the lignin raw material in Example 1. It can be seen that at 1608 cm -1 and 1706cm -1 The absorption peaks near 1138 cm-1 are attributed to the stretching vibrations of C==C and C==O, respectively. It is worth noting that after carbonization and NTP modification, -1 , 1031cm -1 and 619cm -1The absorption peaks at 3423cm correspond to the stretching vibrations of S==O, S—O and C—S, which proves that NTP modification successfully grafted -SO3H onto the surface of solid acid. -1 and 2922cm -1 The reduction or disappearance of the absorption peak at can be attributed to the weakening of the stretching of -OH and the breakage of C-O-C and C-H at high temperature, respectively.
[0058] Example 5: Recycling performance of solid acid catalyst
[0059] Weigh 1 g of fructose into 25 mL of reaction solution, the ratio of solvent (DMSO) to water in the reaction solution is 6:1, add 0.3 g of lignin carbon-based solid acid catalyst obtained in Example 1, the reaction temperature is 180°C, react for 25 minutes, and after the reaction is completed, quickly transfer the reactor to an ice water bath for rapid cooling. After cooling to room temperature, open the reactor. Filter the reaction solution to separate the catalyst, and repeatedly elute with ethanol and deionized water to remove impurities and residues. Recycle five times, and use high performance liquid chromatography to determine the 5-hydroxymethylfurfural content and the amount of residual fructose in the reaction solution. The results are as follows Figure 4 As shown, the fructose conversion rate remained above 97.8%, while the yield of 5-hydroxymethylfurfural gradually decreased from 88.9% to 75.1%, still maintaining a high yield, indicating that the solid acid catalyst has good catalytic stability and reusability.
[0060] It can be seen that the solid acid catalyst prepared by the present invention has the advantages of short preparation time, low pollution, high catalytic efficiency, and recyclability. It can be used to catalyze the conversion of fructose solution into 5-hydroxymethylfurfural with a yield of 70% to 90%. The use of the solid acid catalyst in the reaction process avoids the corrosion of the reaction kettle equipment by the inorganic acid catalyst, and is an environmentally friendly catalyst.
Claims
1. A method for preparing a solid acid catalyst, characterized in that: The preparation method comprises the following steps: Carbonizing lignin to obtain a carbon-based carrier; The carbon-based carrier is placed in a plasma modification instrument, evacuated, and then gas is introduced for activation treatment to obtain a lignin carbon-based material; The lignin carbon-based material is subjected to sulfonation treatment to obtain the solid acid catalyst.
2. The preparation method according to claim 1, characterized in that: The equipment used for the carbonization treatment is a muffle furnace, the temperature is set to 300° C., and the carbonization time is 3 h to 5 h.
3. The preparation method according to claim 1, characterized in that: After the vacuum is evacuated, the vacuum degree in the plasma modification instrument is 5 Pa.
4. The preparation method according to claim 1, characterized in that: The gas used for the activation treatment is selected from at least one of oxygen, nitrogen, carbon dioxide and air; when the gas is introduced for activation treatment, the vacuum degree in the plasma modification instrument is 20Pa, the RF power is set to 160W, and the treatment time is 3min to 5min.
5. The preparation method according to claim 1, characterized in that: The gas used in the sulfonation treatment is sulfur dioxide. During the sulfonation treatment, the vacuum degree in the plasma modification instrument is 20Pa to 50Pa, the radio frequency power is set to 140W to 170W, and the treatment time is 2min to 8min.
6. The preparation method according to claim 5, characterized in that: The sulfonation treatment specifically includes: SO2 ventilation volume is 40Pa, the radio frequency power of the plasma modification instrument is 170W, and after treating for 3 minutes, the lignin carbon-based material is turned over and treated for another 3 minutes.
7. The solid acid catalyst prepared by the method for preparing the solid acid catalyst according to any one of claims 1 to 6.
8. Use of the solid acid catalyst as claimed in claim 7 in the field of preparing 5-hydroxymethylfurfural.
9. The use according to claim 8, characterized in that: The preparation of 5-hydroxymethylfurfural comprises the following steps: 1) adding fructose and the solid acid catalyst into a solvent, mixing, and heating in a sealed container for reaction; 2) cooling the sealed container to room temperature by ice bath, and then filtering to separate the solid and the liquid to obtain the 5-hydroxymethylfurfural; Wherein, the solvent comprises an organic solvent and water in a volume ratio of 4:1 to 6:1; The organic solvent is selected from at least one of dimethyl sulfoxide, acetone, tetrahydrofuran, and methyl isobutyl ketone; The temperature of the heating reaction is 160° C. to 190° C., and the reaction time is 5 min to 100 min.
10. The use according to claim 9, characterized in that: The step also includes washing and drying the obtained solid and then recycling it as a solid acid catalyst; Preferably, the fructose is specifically hexose; Preferably, the mass ratio of the hexose to the solid acid catalyst is 1:(0.01-0.5); Preferably, the amount of the hexose substrate added is 0.02 g / mL to 0.1 g / mL.
Citation Information
Patent Citations
Solid acid catalyst as well as preparation method and application thereof
CN118341447A
Cited By
Carbon-based solid acid-base bifunctional catalyst as well as preparation method and application thereof
CN121869447A